2020
DOI: 10.21203/rs.2.17241/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active and latent tuberculosis in refugees and asylum seekers: a systematic review and meta-analysis

Abstract: Background: In 2018, there were 70.8 million refugees, asylum seekers and persons displaced by wars and conflicts worldwide. Many of these individuals face a high risk for tuberculosis in their country of origin, which may be accentuated by adverse conditions endured during their journey. Objective: We summarised the prevalence of active and latent tuberculosis infection in refugees and asylum seekers through a systematic literature review and meta-analyses by country of origin and host continent. Methods: Art… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Majority (>86%) of refugees are from and stay within developing countries where the TB burden is higher [12]. Studies have shown an increase in the prevalence of TB [13,14] and TB case notification [14,15] when the number of refugee population increases. Thus, key populations such as refugees have been given special focus in the Stop TB [16] and End TB [2] WHO strategic documents so as to achieve the global targets by 2035.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Majority (>86%) of refugees are from and stay within developing countries where the TB burden is higher [12]. Studies have shown an increase in the prevalence of TB [13,14] and TB case notification [14,15] when the number of refugee population increases. Thus, key populations such as refugees have been given special focus in the Stop TB [16] and End TB [2] WHO strategic documents so as to achieve the global targets by 2035.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned pieces of evidence [13][14][15][16][17] indicate that TB is one of the main health problems in the refugee camps of Sudan. Hence, periodic review of TB program performance in the refugee camps is needed to address the gaps and improve the implementation of TB care and prevention program.…”
Section: Introductionmentioning
confidence: 99%
“…The total end year refugee population in Ethiopia was continuously increased from 491030 in 2014 to 728000 by 2017. The highest refugee population by 2017 were in Gambella refugee area (219,708), followed by Dollo Ado (197.952), Shire (109, 360), Asossa (55.726), Jijiga (35,024), Afar (15.390), and Mizan (11,761) [15].…”
Section: Study Settingsmentioning
confidence: 99%
“…Usually, majority (> 85%) of refugees originate from and remain within countries with high burdens of TB [10]. However, according to a recent systemic review and meta-analysis, TB prevalence in refugees and asylum seekers varied more according to countries of origin than the host continent [11]. Other also reported, an association between immigration and increased prevalence of either TB or EPTB [12].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, majority (> 85%) of refugees originate from and remain within countries with high burdens of TB [10]. A recent systemic review and meta-analysis showed that TB prevalence in refugees and asylum seekers varied more according to countries of origin than the host country [11], whereas others reported association between continuous immigration (increase in migrant population) and increase in prevalence of PTB and EPTB [12], in TB case noti cation [13] and in case detection rate [14].…”
Section: Introductionmentioning
confidence: 99%